2015
DOI: 10.3892/mmr.2015.3868
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase 5 regulates the proliferation, motility and invasiveness of lung cancer cells through its effects on cytoskeletal remodeling

Abstract: Abstract. Determining the molecular phenotype is a key to understanding and predicting the metastatic potential and the prognosis for patients with lung cancer. Our previous study demonstrated that increased expression of cyclin-dependent kinase 5 (CDK5) in patients with non-small cell lung cancer (NSCLC) is associated with a poorer prognosis. The present study aimed to further investigate the underlying mechanism of CDK5 in vitro and in vivo using the A549 human NSCLC cell line. A 3-(4,5-dimethylthiazol-2-yl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Similarly, Liu JL. Et al.’s study on CDK5 and lung cancer revealed a similar CDK5 proliferation and apoptosis trend in lung cancer cell lines when CDK5 activity was suppressed by siRNA [ 29 ]. A paradoxical mechanism of CDK5 in HCC was previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Liu JL. Et al.’s study on CDK5 and lung cancer revealed a similar CDK5 proliferation and apoptosis trend in lung cancer cell lines when CDK5 activity was suppressed by siRNA [ 29 ]. A paradoxical mechanism of CDK5 in HCC was previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Cdk5 has indeed been implicated in resistance to PARP inhibitors [16, 32, 34, 39], topoisomerase inhibitors and DNA crosslinkers. In line with these observations, treatment of the NSCLC cell line, A549, the proliferation of which is driven by Cdk5 [11], with the Cdk5 inhibitor, roscovitine, enhanced its sensitivity to IR [40]. In all cases, Cdk5 inhibition or Cdk5 knock-down restored chemotherapeutics sensitivity.…”
Section: Cdk5 In Dna Repair and Drug Resistancementioning
confidence: 91%
“…Second, mRNA and protein expression levels of Cdk5 and its activators are increased, or decreased, in several forms of cancer and these alterations are correlated with cancer severity (Figure 1a, Key Figure; Table 1). For example, Cdk5 and p35/p25 are elevated in pulmonary neuroendocrine cancers [911], in sporadic and familial forms of medullary thyroid carcinoma (MTC) [12] and pituitary adenoma [13]. In fact Cdk5 and p35/p25 expression appear to typify neuroendocrine cancer pathology.…”
Section: Human Cancers Express Cdk5mentioning
confidence: 99%
“…Interestingly, CDK5 activity is required for cell invasion in prostate carcinoma, glioblastoma multiforme [2], pancreatic cancer [3], medullary thyroid cancer [4]. Inhibition of CDK5 activity decreases lung cancer cell motility [5]. Liu et al have also reported that increased CDK5 expression in patients with non-small cell lung cancer is correlated with poor prognosis [6].…”
Section: Introductionmentioning
confidence: 99%